2006
DOI: 10.1089/aid.2006.22.589
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Consumption Results in Higher Simian Immunodeficiency Virus Replication in Mucosally Inoculated Rhesus Macaques

Abstract: The influence of alcohol consumption on HIV pathogenesis is not well understood. In this study we used the SIV/macaque model of HIV infection to study the influence of chronic binge alcohol consumption on simian immunodeficiency virus (SIV) infection. Rhesus macaques were fed alcohol or isocaloric amounts of sucrose via indwelling intragastric catheters and then inoculated with SIVmac251 by the rectal route. Real-time RTPCR for SIV gag mRNA showed significantly higher plasma viral copies in alcohol-consuming m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 21 publications
8
35
0
Order By: Relevance
“…Overall, chronic ethanol selfadministration did not modulate the frequency or subset distribution of circulating lymphocytes. This observation is consistent with some reports of chronic ethanol exposure in rodents, NHPs and humans [8,34,35]. Nonetheless, other studies have reported significant perturbations of both the number and frequency of peripheral T and B cells with either acute or chronic alcohol exposure (reviewed by [34,36]).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, chronic ethanol selfadministration did not modulate the frequency or subset distribution of circulating lymphocytes. This observation is consistent with some reports of chronic ethanol exposure in rodents, NHPs and humans [8,34,35]. Nonetheless, other studies have reported significant perturbations of both the number and frequency of peripheral T and B cells with either acute or chronic alcohol exposure (reviewed by [34,36]).…”
Section: Discussionsupporting
confidence: 92%
“…As previously described in humans and animal models [1,2,4,6,8,[37][38][39][40], our results indicate heavy chronic ethanol consumption impairs several key aspects of vaccine-elicited immune responses including T and B cell proliferation, T cell cytokine production and antibody secretion. Importantly our data suggest that recall responses to vaccines received prior to alcohol consumption might also be compromised.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding may reflect that, in the absence of HIV infection, TD T cells may be slowly lost through activation-induced death in the presence of genital inflammation, while CD45RA Ϫ CCR7 ϩ CM T cells are recruited to replenish the diminishing CD4 T cell pool. Although CD45RA Ϫ CCR7 ϩ CM T cells are not common at mucosal sites and their identification was surprising, CM cells that were identified in the mucosal effector sites in macaques have been proposed to be "reserve" antigen-experienced cells that are in a "quasiresting" state awaiting another exposure to the antigen of original stim- (38). Despite evidence that inflammatory cytokines may alter the differentiation status of T cells in an antigenindependent manner (12,42), the association between inflammatory cytokines in genital secretions and differentiation of individual T cell subsets isolated from the cervix was not evident in HIV-infected women in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The higher viral load and accelerated disease progression occured despite CBA-administered animals having greater virus-specific cellular immune responses and similar humoral responses compared to a sucrose-treated group (Pahar et al 2013). A possible mechanism for the enhanced viral replication may be alcohol-mediated alterations in the gut mucosal immune system, as there were higher percentages of central memory and naïve CD4+ T cells in duodenal tissues of CBA macaques prior to SIV inoculation (Poonia et al 2006a). After infection, CBA animals had higher levels of SIV in the gut mucosa sampled at viral set point (approximately 10 weeks post-inoculation) (Poonia et al 2006b).…”
Section: Introductionmentioning
confidence: 99%